Implementation of Learning Management to Improve the Quality of Education at Islamic Junior High School - Maskumi Maskumi; Ihsan Mustofa; Ehwanudin Ehwanudin (CV. Bimbingan Belajar Assyfa, 2025)
This study aims to analyze the implementation of learning management in improving the quality of education at MTs Al-Anshor Ketapang, South Lampung Regency. The research focuses on three main functions of learning management: planning (planning), implementation (actuating), and evaluation (controlling). This study employed a qualitative approach with a descriptive type. Data were collected through in-depth interviews, participatory observation, and documentation. The informants included the madrasah principal, vice principal for curriculum, teachers, and students. Data validity was ensured through source triangulation, technique triangulation, and time triangulation. Data analysis used the Miles and Huberman model: data reduction, data display, and conclusion drawing. The results showed that: (1) learning management has been implemented through planning, implementation, and evaluation, but is not yet fully optimal. Planning is still administrative and less contextual; implementation is still teacher-centered with limited methods; evaluation focuses on cognitive aspects without adequate follow-up. (2) Learning management contributes to improving the quality of education in terms of process order, learning outcomes, and discipline, but its effectiveness is not yet optimal due to gaps between planning and implementation. (3) Supporting factors include the availability of learning tools, principal support, teacher commitment, and student enthusiasm; inhibiting factors include limited variation in teaching methods, inadequate facilities, heterogeneity of student abilities, time constraints, and lack of evaluation follow-up. This study concludes that strengthening the integration of planning, implementation, and evaluation is essential for optimizing learning management and improving educational quality.